Implementation of the A+ schools program: An examination of baseline teacher perceptions and instructional behaviors - Miller, Rachelle; Wake, Donna; Whittingham, Jeff L. (Journal of Interdisciplinary Studies in Education, 2016)
In a baseline study of teachers’ attitudes towards arts integration, elementaryteachers (23 experimental; 23 control) in grades K-6 indicated they valued artsintegration and were willing to integrate the arts in their classrooms with nosignificant differences between groups. Additional analysis of teachers’instructional behaviors with structured protocols prior to programimplementation showed that teachers from the control school demonstratedsignificantly higher uses of interdisciplinary curricula planning, experientiallearning, and critical thinking. These data indicate that schools choosing toadopt an arts integrated curricula may be predisposed to the concepts underlyingeffective arts integration; they may also recognize their need for support inimplementing arts integrated curricula via structured program implementationand suppor